2014
DOI: 10.1016/j.compchemeng.2014.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of control techniques for the dynamic optimization of (semi-)batch reactors

Abstract: This work investigates how batch reactors can be optimized to increase the yield of a desired product coupling two appealing techniques for process control and optimization: the nonlinear model predictive control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In practice, MPC has been recognized as the only one among advanced control techniques (defined as techniques more advanced than the PID method) which has been exceptionally successful in numerous practical applications [24]. By coupling real-time optimization (RTO) with nonlinear MPC (NMPC), the resulting paradigm of RTO-NMPC allows dealing with nonlinearities in process dynamics and solving effectively and simultaneously the quadratic problem and economic problem [25,26]. However, NMPC encounters a lot of limitations such as difficulties in building accurate dynamic models, the computational time that has to ensure real-time feasibility, the complexity of online implementation, and the insufficient accuracy of online solutions [2,27], which limits its applications to bioprocesses.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, MPC has been recognized as the only one among advanced control techniques (defined as techniques more advanced than the PID method) which has been exceptionally successful in numerous practical applications [24]. By coupling real-time optimization (RTO) with nonlinear MPC (NMPC), the resulting paradigm of RTO-NMPC allows dealing with nonlinearities in process dynamics and solving effectively and simultaneously the quadratic problem and economic problem [25,26]. However, NMPC encounters a lot of limitations such as difficulties in building accurate dynamic models, the computational time that has to ensure real-time feasibility, the complexity of online implementation, and the insufficient accuracy of online solutions [2,27], which limits its applications to bioprocesses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sen et al designed an efficient control system for the continuous production of active pharmaceutical ingredients which incorporated the control scheme of unit operations crystallization, filtration, drying and so on . Batch reactors control techniques had also been designed and assessed thoroughly to improve the performance . Singh et al had designed a system-side proportional–​integral–​derivative (PID) control strategy and demonstrated the improved performance of manufacturing process with the controllers compared to the open loop simulations.…”
Section: Introductionmentioning
confidence: 99%
“…28 Batch reactors control techniques had also been designed and assessed thoroughly to improve the performance. 29 Singh et al had designed a system-side proportional− integral−derivative (PID) control strategy and demonstrated the improved performance of manufacturing process with the controllers compared to the open loop simulations. They proposed another hybrid model predictive control (MPC)-PID control scheme for the continuous pharmaceutical tablet manufacturing process after about one year.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, many authors focused on batch processes to find efficient solutions to make them more automatic and better controlled. Most of the times model-based control techniques (proposed for the first time in ref ) have been used with the aim of improving safety and optimizing intrinsically batch operations. Several authors have also shown the potential for applying the dynamic optimization to batch systems, studying in detail even the most appropriate control methodology to be selected and employed. , Moreover, both for optimal control and dynamic optimization, the best ways to perfom the process modeling have also been addressed …”
Section: Introductionmentioning
confidence: 99%